The Emergence of a New Superpower Rivalry and the Vulnerabilities of the United Nations Security Council - Choi, Min Seok; Chang, Sungwon (Technium Social Sciences Journal, 2024)
Throughout the past decade, the People’s Republic of China has experienced rapid economic and military growth, increasing its influence in Asia. With the abandonment of its ‘biding time’ approach in its foreign policy, China has transformed into a competitive challenger against the American hegemony, engendering a new geopolitical rivalry. This newly emerging rivalry threatens the United Nations’ effectiveness as it exposes numerous structural flaws of the United Nations. A binary atmosphere is slowly encroaching the United Nations Security Council, causing the council to be further polarised. Certain vulnerabilities of the Security Council often cause the council to be effectively paralysed, forcing the UN to be unable to respond to global conflicts. This paper evaluated three different proposed structural flaws of the council through case studies and data analyses and offered recommendations accordingly. The United Nations must amend the structure of the Security Council in order to continue to effectively maintain international peace and avoid repeating the failure of its predecessor, the League of Nations